The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1139/cjce-2021-0162
|View full text |Cite
|
Sign up to set email alerts
|

A case study of PavMD a new tool to identify good performing pavements in New Zealand

Abstract: With the advancement of digital technology, the collection of pavement performance data has become commonplace. The improvement of tools to extract useful information from pavement databases has become a priority to justify expenditures. This paper presents a case study of PaveMD, a tool that integrates multi-dimensional data structures with a data-driven fuzzy approach to identify good performing pavement sections. Combining this tool with an innovative paradigm where the focus is on repeating success can bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…The Internet of Things (also known as IoT) is a novel potential avenue to collect data to investigate this problem. IoT is an approach of using a network of tiny low-cost sensors for data collecting, analysis, real-time data visualization and real-time communication (Abu-Elkheir et al 2013, Hendricks 2015, Kim et al 2017, Van der Walt et al 2022. This study aims to extend the work by Van der Walt (2017) and improve the information available to calibrate the TVAS, for local NZ conditions (Van der Walt et al 2017, Van der Walt et al 2018.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Internet of Things (also known as IoT) is a novel potential avenue to collect data to investigate this problem. IoT is an approach of using a network of tiny low-cost sensors for data collecting, analysis, real-time data visualization and real-time communication (Abu-Elkheir et al 2013, Hendricks 2015, Kim et al 2017, Van der Walt et al 2022. This study aims to extend the work by Van der Walt (2017) and improve the information available to calibrate the TVAS, for local NZ conditions (Van der Walt et al 2017, Van der Walt et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…IoT is an approach of using a network of tiny low-cost sensors for data collecting, analysis, real-time data visualization and real-time communication (Abu-Elkheir et al 2013, Hendricks 2015, Kim et al 2017, Van der Walt et al 2022. This study aims to extend the work by Van der Walt (2017) and improve the information available to calibrate the TVAS, for local NZ conditions (Van der Walt et al 2017, Van der Walt et al 2018. Specifically, the LWD on straight regional (50km/h) roads that have painted shoulder and centerline markings with no parked vehicles (Category 1 roads) versus the same road type with parked vehicles (Category 2 roads) will be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Rutting is a common deterioration mode of flexible pavement structures resulting from repeated load applications along the wheel paths (2)(3)(4)(5)(6)(7)(8)(9)(10). Previous research has suggested that there may be feedback loops in the causal mechanisms through which rutting and driver position (lateral wander) interrelate.…”
mentioning
confidence: 99%